Seas Opportunity: Understanding The Blue Economy Landscape In The MENA Region - Haura, Inas Alya; Ardianto, Fetra (Department of International Relations, Universitas Brawijaya, 2024)
This paper aims to investigate the emerging blue economy landscape in the Middle East and North Africa (MENA) region. Furthermore, this paper seeks to explore various dimensions of sustainable marine resource management and initiatives undertaken by MENA countries to exploit blue economy opportunities. As the MENA region advances in developing its blue economy, this study seeks to offer comprehensive insights into marine resource utilization, sustainable development principles, and increased regional collaboration in fostering a strong blue economy framework. By analyzing current practices, this research seeks to contribute to a deeper understanding of how the MENA region can effectively integrate blue economy principles into national policies, improve marine infrastructure, and build cooperative frameworks for environmental protection and economic growth.